Analysis of the Functional Polymorphism in the Cytochrome P450 CYP2C8 Gene rs11572080 with Regard to Colorectal Cancer Risk - Ladero, José M.; Agúndez, José A.; Martínez, Carmen; Amo, Gemma; Ayuso, Pedro; García-Martín, Elena (Frontiers in Genetics, 2012)
In addition to the known effects on drug metabolism and response, functional polymorphisms of genes coding for xenobiotic-metabolizing enzymes (XME) play a role in cancer. Genes coding for XME act as low-penetrance genes and confer modest but consistent and significant risks for a variety of cancers related to the interaction of environmental and genetic factors. Consistent evidence supports a role for polymorphisms of the cytochrome P450 CYP2C9 gene as a protecting factor for colorectal cancer susceptibility. It has been shown that CYP2C8 and CYP2C9 overlap in substrate specificity. Because CYP2C8 has the common functional polymorphisms rs11572080 and rs10509681 (CYP2C8*3), it could be speculated that part of the findings attributed to CYP2C9 polymorphisms may actually be related to the presence of polymorphisms in the CYP2C8 gene. Nevertheless, little attention has been paid to the role of the CYP2C8 polymorphism in colorectal cancer. We analyzed the influence of the CYP2C8*3 allele in the risk of developing colorectal cancer in genomic DNA from 153 individuals suffering colorectal cancer and from 298 age- and gender-matched control subjects. Our findings do not support any effect of the CYP2C8*3 allele (OR for carriers of functional CYP2C8 alleles = 0.50 (95%CI = 0.16-1.59; p = 0.233). The absence of a relative risk related to CYP2C8*3 did not vary depending on the tumor site. We conclude that the risk of developing colorectal cancer does not seem to be related to the commonest functional genetic variation in the CYP2C8 gene.